India's Evolving engagements in the Arctic. (2nd January 2021) - Agarwala, Nitin
ABSTRACT: The Arctic has attracted world attention in recent years as global warming began melting the sea ice at a much faster rate than recorded after 1979, the year when record-keeping began for the region. This new-found attention is also linked with greater accessibility of the Arctic Ocean, which is creating a geopolitical competition for resources and control. So far, the world media has focused primarily on the efforts of China in the Arctic due to its economic might, resulting in numerous academic literature. In comparison, the efforts of India in the Arctic have been relatively lesser researched and discussed. Those available have provided conflicting and sometimes debating opinions. It is with this understanding that the article discusses India's past and present engagement in the Arctic, with possible future trends and recommendations for India's evolving engagements in this region.